High-dose MRI-Guided Adaptive Radiation Therapy for Locally Recurrent Pancreatic Cancer - Hama, Yukihiro; Tate, Etsuko (Reports of Radiotherapy and Oncology, 2022)
Introduction: The prognosis of recurrent pancreatic cancer is poor even after curative resection. There have been no reports of MRI-guided radiation therapy for locally recurrent pancreatic cancer after curative resection and chemotherapy. Case Presentation: A 66-year-old man with pancreatic cancer was referred to our institution for local recurrence after failure of surgical resection and second-line chemotherapy. He did not want to undergo further chemotherapy, so high-dose MRI-guided adaptive radiation therapy was performed in daily doses of 2.5 Gy to a total dose of 70 Gy over a period of 5.5 weeks. Three months after radiation therapy, the recurrent tumors disappeared and his CA19-9 level was within normal range without chemotherapy. There were no adverse events during treatment and three months of follow-up. Conclusions: High-dose MRI-guided adaptive radiation therapy may be safe and useful for locally recurrent pancreatic cancer.